AN INVESTIGATION INTO VISITOR ATTRACTION ARTICLES IN ENGLISH AND VIETNAMESE ELECTRONIC NEWSPAPERS - Ph. D. Nguyễn Quỳnh Hoa (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Undeniably, with the trend of global tourism, people have more chances to explore different places all over the world. In fact, the number of people who get access to the internet to search for visitor attraction articles has been on the rise. Unsurprisingly, such advertising articles attract from freelance journalists to professional copywriters. In reality, much has been written about discourse analysis, but little has been done about advertising, especially the discourse of VAAs. Therefore, the study entitled “An Investigation into Visitor Attraction Articles in English and Vietnamese Electronic Newspapers” is carried out to discover the similarities and differences between English and Vietnamese visitor attraction articles in terms of their layout features, syntactic features, lexical features and stylistic devices between EVAAs and VVAAs. The analysis is based on 300 samples in VAAs (150 in English and 150 in Vietnamese) collected from popular and prestigious online newspapers in the United States and Vietnam. On the basis of the findings, the thesis sets out some implications and suggestions for teaching and learning both languages. The research result can be useful for teachers, copywriters, freelances and learners of English, as well as those who are interested in advertising, especially visitor attraction articles.